NASA GEOS Composition Forecast Modeling System GEOS‐CF v1.0: Stratospheric Composition. (7th June 2022) - Knowland, K. E.; Keller, C. A.; Wales, P. A.; Wargan, K.; Coy, L.; Johnson, M. S.; Liu, J.; Lucchesi, R. A.; Eastham, S. D.; Fleming, E.; Liang, Q.; Leblanc, T.; et al.
Abstract: The NASA Goddard Earth Observing System (GEOS) Composition Forecast (GEOS‐CF) provides recent estimates and 5‐day forecasts of atmospheric composition to the public in near‐real time. To do this, the GEOS Earth system model is coupled with the GEOS‐Chem tropospheric‐stratospheric unified chemistry extension (UCX) to represent composition from the surface to the top of the GEOS atmosphere (0.01 hPa). The GEOS‐CF system is described, including updates made to the GEOS‐Chem UCX mechanism within GEOS‐CF for improved representation of stratospheric chemistry. Comparisons are made against balloon, lidar, and satellite observations for stratospheric composition, including measurements of ozone (O3 ) and important nitrogen and chlorine species related to stratospheric O3 recovery. The GEOS‐CF nudges the stratospheric O3 toward the GEOS Forward Processing (GEOS FP) assimilated O3 product; as a result the stratospheric O3 in the GEOS‐CF historical estimate agrees well with observations. During abnormal dynamical and chemical environments such as the 2020 polar vortexes, the GEOS‐CF O3 forecasts are more realistic than GEOS FP O3 forecasts because of the inclusion of the complex GEOS‐Chem UCX stratospheric chemistry. Overall, the spatial patterns of the GEOS‐CF simulated concentrations of stratospheric composition agree well with satellite observations. However, there are notable biases—such as low NO x and HNO3 in the polar regions and generally low HCl throughout the stratosphere—and future improvements to the chemistry mechanism and emissions are discussed. GEOS‐CF is a new tool for the research community and instrument teams observing trace gases in the stratosphere and troposphere, providing near‐real‐time three‐dimensional gridded information on atmospheric composition. Plain Language Summary: In the stratosphere, the ozone layer protects life on Earth from harmful ultraviolet, "UV, " radiation. Chemical loss of this protective ozone occurs each year over Antarctica and occasionally over the Arctic during spring when air over these regions are cut‐off from the rest of the stratosphere because of the strong winds blowing circularly around the pole. For accurate forecasting of the ozone layer and UV, it is critical to have both meteorology and chemistry accurately represented in forecast models. NASA's Goddard Earth Observing System composition forecast, "GEOS‐CF, " produces global 5‐day forecasts of weather and atmospheric trace gases that are important for tracking the chemical interactions in the full atmosphere. Additionally, weather systems can bring down stratospheric ozone toward the Earth's surface where ozone is a regulated air pollutant. GEOS‐CF can differentiate between ozone enhancements at the Earth's surface that result from pollution and from stratosphere‐to‐troposphere transport, improving the forecasts of stratospheric‐influenced ozone exceedance events. This study describes the GEOS‐CF model system and evaluates the modeled representation of stratospheric trace gases. GEOS‐CF products are used to support NASA ground and satellite‐based instrument teams as well as field and aircraft campaigns that measure trace gases throughout the atmosphere. Key Points: Demonstrate the GEOS‐CF system is capable of supporting NASA science missions and applications which observe stratospheric composition The GEOS‐CF model produces realistic stratospheric ozone forecasts, a new capability during anomalous polar vortex conditions Spatial patterns of the GEOS‐CF simulated concentrations of stratospheric composition agree well with independent observations